The development, initial implementation and support of a primary health care training programme in rational drug use - Orrell, Catherine Jane (Division of Clinical Pharmacology, 2017)
The Rational Drug Use Training Project is a district-oriented programme designed to improve rational drug use among primary health care prescribers in the South African public sector. This thesis describes the development of the project and details the initial implementation study in 3 facilities in Region B of KwaZulu-Natal. This was a small before-after study, with no control. There were three components: 1. A series of easily collectable drug use indicators, adapted from those developed by WHO/INRUD. These allow primary health care staff to monitor their prescribing patterns in a district or facility. Ninety sets of prescribing indicators were collected as a baseline at 3 facilities in KwaZulu-Natal in December 1996, by the district trainers and the Rational Drug Use Training Project staff. The process was repeated in March 1997, after the training intervention, by the district trainers alone. 2. The intervention was a 2-day training workshop in rational drug use. This is problem-based and trained on-site in primary health facilities. Training was done by 8 district trainers from Region B who were taught to present the workshop by the Rational Drug Use Training Project staff. The workshop covers principles of prescribing, use of standard treatment guidelines, principles of clinic stock management and principles of good dispensing. Staff are encouraged to develop their self-learning skills through questioning, and seeking answers to clinical and drug related queries. 3. A set of resources, including texts, treatment guidelines and information centres, to provide quality, safe and unbiased drug information, are made accessible to staff at primary care level. These are available by post, telephone or e-mail. The Primary Care Medicines Resource Centre at the University of Durban-Westville was developed as a result of this study. Significant improvements in prescribing habits were noticed after the study. There was an increase in the percentage of drugs prescribed by their generic names (p=0.000); an increase in the number of medications adequately labelled (p=0.0132); a decrease in the cost of prescriptions (p=0.0134); and a decrease in the number of prescriptions that did not follow standard treatment guidelines at all for that diagnosis (p=0.0109). The Mann-Whitney U- test was used for statistical analysis. There were no significant changes in the average number of drugs per prescription; the percentage of drugs from the Essential Drugs List; and the number of prescriptions that completely followed standard treatment guidelines. Qualitative feedback was favourable too. This was a difficult study to undertake. The staff and funding organisation, Health Systems Trust, fell outside of the provincial health structure and met resistance at that level. Regional politics shaped the programme's design. District trainers needed for the cascade approach were not available. District staff remained entrenched in a traditional health hierarchy and found it difficult to function as a team. The will of district prescribing staff to learn was low. Rational drug use training is only one of a number of essential elements of in-service training urgently needed by these staff. Despite these problems, quantitative and qualitative success was shown. The Training Manual, developed in support of the training, has been in demand. The Primary Care Medicines Resource Centre is growing. Primary care prescribers have been motivated to monitor their own practices and manage their own clinic stock. The project is a successful example of multi-disciplinary and institutional collaboration. The Rational Drug Use Training Project has expanded to eight other health districts in 1997. A list of criteria, such as the need for a district trainer, have been set. These must be met by the district before training will commence. The project is a resource for Initiative for Sub-District Support, a joint district development programme of Health System Trust and the Department of Health. Most expansion in 1998 will be through this initiative. The difficulties encountered and achievements made during this small study will be used to support, and hopefully strengthen, the development of the primary health care oriented district health system, so urgently needed by the South African population.